THE ROLE OF THE PRODUCER IN THE PRODUCTION OF THE FEATURE PROGRAM 'BACKSTAGE' EPISODE 'BEHIND THE SCENES OF THEATER ARTS - Bumi Respati, Moehamad Gentar; Irawan, Rahmat Edi (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
This "BACKSTAGE" program is a feature format television program. This Backstage program will discuss all things related to behind the scenes of an event. This program is also very interesting because Backstage itself is a VIP area, not everyone can see and enter the Backstage area. This research has three benefits, namely general benefits, practical benefits and theoretical benefits. as for the purpose of this research is to provide information to the audience both those who watch and those who read this journal the importance of preparations made and prepared to support the smooth running of a Theater Arts. The creator of the work as a Producer creates an event program entitled "BACKSTAGE" in the making of this work is divided into three stages, namely pre-production, production and post-production. in addition to having full rights to a production, Producers also have duties in preparing an idea, conducting research, developing ideas, finding talent, recce, preparing tools, assisting the reading process, licensing production locations, preparing tools needed by each department and making production plans starting from schedules, drafting budgets, job descriptions, and real budgeting. In addition, the producer also controls during the filming and editing process, consumption, prepares accommodation and To avoid over time during the production process, the Producer makes a crew call that is adjusted to the hourly needs of each department.